2000
DOI: 10.1095/biolreprod63.2.508
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Inhibitory Factor, Leukemia Inhibitory Factor Receptor, and Glycoprotein 130 in Rhesus Monkey Uterus During Menstrual Cycle and Early Pregnancy1

Abstract: This goal of this study was to examine immunohistochemical distribution of leukemia inhibitory factor (LIF), LIF receptor (LIFR), and glycoprotein (gp) 130 in rhesus monkey uterus during the menstrual cycle and early pregnancy. Pregnancy rate was significantly reduced in the control group from 66.7% (12 of 18) to 22.2% (4 of 18) with an injection of goat anti-human recombinant LIF immunoglobulin G into the uterine lumen on Day 8 of pregnancy. LIF was mainly localized in glandular and luminal epithelium. LIF im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 20 publications
2
28
0
2
Order By: Relevance
“…After the initiation of implantation, however, both Lif-r and gp130, but not their ligand, were expressed in decidual cells surrounding the implanting embryo. This pattern of uterine Lif-r and gp130 localization around the time of implantation was very similar to that reported in the mouse (Cheng et al 2001, Ni et al 2002, human (Cullinan et al 1996), and monkey (Yue et al 2000). The co-localization of Lif-r and gp130 in periimplantation decidual cells suggests that Lif action is important for decidualization.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…After the initiation of implantation, however, both Lif-r and gp130, but not their ligand, were expressed in decidual cells surrounding the implanting embryo. This pattern of uterine Lif-r and gp130 localization around the time of implantation was very similar to that reported in the mouse (Cheng et al 2001, Ni et al 2002, human (Cullinan et al 1996), and monkey (Yue et al 2000). The co-localization of Lif-r and gp130 in periimplantation decidual cells suggests that Lif action is important for decidualization.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, another study has demonstrated E-induced Lif-r expression in the trabecular bone (Lindberg et al 2002). Using immunocytochemical localization of proteins, several studies have demonstrated in the human and monkey uterus that Lif-r and gp130 localization during the luteal phase were stronger than their localization during the proliferative phase (Yue et al 2000, Classen-linke et al 2004. The most intense immunostaining of IL-11 was also seen in decidualized stromal cells in the mid-and late-secretory phases in human uterus (Dimistriadis et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-LIF polyclonal antibodies administered directly into the uterus interfere with blastocyst implantation in the rhesus monkey (24) and in the mouse (25), but neither method completely prevents implantation. Intrauterine injection of a cell-permeable STAT3 peptide inhibitor (26) or a STAT3 decoy oligodeoxynucleotide (27) achieved Ϸ70% reduction in implantation rates.…”
Section: Discussionmentioning
confidence: 99%
“…P values lower than 0.05 were considered statistically significant. To estimate specific staining in various cells of the uteri, a semi-quantitative subjective scoring was also performed by three blinded investigators using a 4-scale system with -(nil), +/-(weak), + (moderate), and ++ (strong), as described by Yue et al [36]. The statistical data of Western blot from three individual experiments were analyzed by using Statistical Package for Social Science (SPSS for Windows package release 10.0, SPSS Inc., Chicago, IL).…”
Section: Microscopic Assessment and Statistical Analysismentioning
confidence: 99%